Pengaruh Persepsi Risiko Bencana Tsunami dan Citra Destinasi Terhadap Niat Berkunjung Kembali Wisatawan ke Pantai Anyer Banten - Muhammad Nur Ali Darajat; Fitri Rahmafitria; Reiza Miftah Wirakusuma (STIEPAR YAPARI Bandung, 2021)
This study aims to explore the effect of tsunami risk perception and destination image on the intention of returning tourists. The data collection technique used purposive sampling which was distributed to 171 tourists who had visited Anyer Beach. Hypothesis testing was carried out using multiple linear regression through the SPSS 26 for windows program. The results showed that the perception of tsunami risk and the image of the destination in Anyer Beach had a negative effect on the intention to return to Anyer Beach. Although there is no direct influence of perception of tsunami risk on intention to revisit, this study found that the image of the destination was able to reduce the level of tourists' perception of tsunami risk, so that they were willing to revisit disaster-prone destinations.